2020
DOI: 10.1021/acscatal.0c00574
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Interfacial CO2 Activation on Al Doped Cu/ZnO

Abstract: We report on a combined quantitative charge carrier and catalytic activity analysis of Cu/ZnO­(:Al) model catalysts. The promoting effect of Al3+ on the ZnO support for CO2 activation via the reverse water–gas-shift reaction has been investigated. The contact-free and operando microwave Hall Effect technique is applied to measure charge carriers in Cu/ZnO­(:Al) based model catalysts under reverse water–gas shift reaction conditions. This method allows us to monitor the electrical conductivity, charge carrier m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…The chemical nature of Zn was found to play an essential role in CO 2 hydrogenation to methanol Figure C shows the XAES spectra of Zn LMM in the treated catalysts, and there were two peaks at around 498 and 495 eV, which were ascribed to Zn 2+ and Zn 0 species, respectively .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The chemical nature of Zn was found to play an essential role in CO 2 hydrogenation to methanol Figure C shows the XAES spectra of Zn LMM in the treated catalysts, and there were two peaks at around 498 and 495 eV, which were ascribed to Zn 2+ and Zn 0 species, respectively .…”
Section: Resultsmentioning
confidence: 97%
“…The chemical nature of Zn was found to play an essential role in CO 2 hydrogenation to methanol. 6 Figure 10C shows the XAES spectra of Zn LMM in the treated catalysts, and there were two peaks at around 498 and 495 eV, which were ascribed to Zn 2+ and Zn 0 species, respectively. 38 It could be found that the surface concentration of Zn species was decreased with the addition of ZrO 2 in these catalysts from the intensity of Zn XAES signals, which should be caused by the strong metal−support interaction.…”
Section: Physical and Structuralmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the chemical nature of Zn was related to the production of methanol in CO 2 hydrogenation. [28] Figure 8B showed the XAES spectra of Zn LMM in the treated catalysts, and there were two peaks around 498 and 495 eV, which were ascribed to Zn 2 + and Zn 0 species, respectively. [29] The presence of Zn 0 species on the treated catalysts should be attributed to the reduction of Zn 2 + species interacted with metallic Cu by the dissociated hydrogen on dispersed Cu, and the binding energy of Zn 0 species was weakened with the increase of ZnO, which probably was ascribed to the electron injection from the ZnO x conduction band to Cu.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11] The catalytic hydrogenation of CO2 produces several important bulk chemicals including formic acid, methanol, and hydrocarbons. 12,13,[22][23][24][14][15][16][17][18][19][20][21] Although this one-step CO2 conversion to value-added chemicals is attractive, there is difficulty associated with the fact that CO2 is kinetically unreactive and thermodynamically stable. 25,26 The catalytic hydrogenation of CO2 to CO, also called the reverse water-gas shift (RWGS: CO2 + H2 → CO +H2O) reaction, serves as a highly flexible strategy for utilization of CO2 because CO is an important intermediate in various well-established catalytic processes to manufacture value-added chemicals.…”
Section: Introductionmentioning
confidence: 99%